2011
DOI: 10.1098/rsif.2011.0177
|View full text |Cite
|
Sign up to set email alerts
|

Role of shear stress and stretch in vascular mechanobiology

Abstract: Blood vessels are under constant mechanical loading from blood pressure and flow which cause internal stresses (endothelial shear stress and circumferential wall stress, respectively). The mechanical forces not only cause morphological changes of endothelium and blood vessel wall, but also trigger biochemical and biological events. There is considerable evidence that physiologic stresses and strains (stretch) exert vasoprotective roles via nitric oxide and provide a homeostatic oxidative balance. A perturbatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
209
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(212 citation statements)
references
References 74 publications
3
209
0
Order By: Relevance
“…Stehbens et al [10] in their histological study of human UVs observed cell debris in the walls of umbilical vessels that could be attributed to hemodynamic stress of the fetoplacental circulation resembling early events of atherogenesis. Lu and Kassab, [15] stated that the vascular walls are subjected to three hemodynamic forces; the blood pressure created by cardiac contraction, the circumferential stretch of the vessel with the cardiac cycle, and the shear stress. Shear stress is the frictional force of the viscous blood on the endothelial surface.…”
Section: Histomorphometric Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stehbens et al [10] in their histological study of human UVs observed cell debris in the walls of umbilical vessels that could be attributed to hemodynamic stress of the fetoplacental circulation resembling early events of atherogenesis. Lu and Kassab, [15] stated that the vascular walls are subjected to three hemodynamic forces; the blood pressure created by cardiac contraction, the circumferential stretch of the vessel with the cardiac cycle, and the shear stress. Shear stress is the frictional force of the viscous blood on the endothelial surface.…”
Section: Histomorphometric Resultsmentioning
confidence: 99%
“…There was no external elastic lamina, adventitia, or vasa vasorum. Endothelial cells of intima showed vacuolations in H&E preparations whereas, it demonstrated positive adhesion molecule 1 (VCAM-1), intercellular adhesion molecule 1 (ICAM-1) and monocyte chemotactic protein 1 (MCP1) [15,17,19] . Recent studies indicate that disturbed blood flow and associated low and reciprocating shear stress induce a sustained activation of some atherogenic genes in endothelial cells like monocyte chemotactic protein-1 (MCP-1) that induces monocyte infiltration into the arterial wall [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple other structures or molecules (e.g., caveolae and G proteins) may also serve as mechanosensors in SMC. 76,80,97,98 Considerably more work remains before we learn enough to allow the stretch response to be selectively manipulated toward investigative and therapeutic ends.…”
Section: Myogenic Vasoconstrictionmentioning
confidence: 99%
“…Finally, increased wall stress causes pathologic remodeling in systemic arteries. [73][74][75][76][77] Note that intravascular pressure is not the only plausible relevant mechanical force. The cross-sectional area of the pulmonary vascular bed is presumably reduced with PVHincreased PVR, implying (absent lower flow) that shear stress is increased.…”
Section: Wall Stress and Pvh-phmentioning
confidence: 99%
“…In fact, it is well known that blood vessels are under constant mechanical loading from flowing blood which cause internal stresses, known as endothelial shear stress (caused by flow) and circumferential stretch (caused by pressure). These mechanical forces not only cause morphological changes of endothelium and blood vessel wall, but also trigger a myriad of intracellular events in endothelial cells and activate biochemical and biological events (Lu & Kassab, 2011). The triggering of endothelial signaling by mechanic forces seems to be mostly determined by the cytoskeleton, which represents a highly dynamic network that constantly assembles and disassembles, playing an active role in responding to mechanical stimuli (Wong et al, 1983).…”
Section: Effects Of Aging On Vascular Functionmentioning
confidence: 99%